Advances in Genetic Engineering Technology and Its Application in the Industrial Fungus Aspergillus oryzae - Jin, Feng-Jie; Hu, Shuang; Wang, Bao-Teng; Jin, Long (Frontiers in Microbiology, 2021)
The filamentous fungus Aspergillus oryzae is an important strain in the traditional fermentation and food processing industries and is often used in the production of soy sauce, bean paste, and liquor-making. In addition, A. oryzae has a strong capacity to secrete large amounts of hydrolytic enzymes; therefore, it has also been used in the enzyme industry as a cell factory for the production of numerous native and heterologous enzymes. However, the production and secretion of foreign proteins by A. oryzae are often limited by numerous bottlenecks that occur during transcription, translation, protein folding, translocation, degradation, transport, secretion, etc. The existence of these problems makes it difficult to achieve the desired target in the production of foreign proteins by A. oryzae. In recent years, with the decipherment of the whole genome sequence, basic research and genetic engineering technologies related to the production and utilization of A. oryzae have been well developed, such as the improvement of homologous recombination efficiency, application of selectable marker genes, development of large chromosome deletion technology, utilization of hyphal fusion techniques, and application of CRISPR/Cas9 genome editing systems. The development and establishment of these genetic engineering technologies provided a great deal of technical support for the industrial production and application of A. oryzae. This paper reviews the advances in basic research and genetic engineering technologies of the fermentation strain A oryzae mentioned above to open up more effective ways and research space for the breeding of A. oryzae production strains in the future.